2011
DOI: 10.1097/mbc.0b013e328343315c
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heparin versus no treatment in women with previous severe pregnancy complications and placental findings without thrombophilia

Abstract: Low molecular weight heparin (LMWH) treatment has been recommended for pregnant women with previous adverse pregnancy and who were diagnosed as having a thrombophilia. We now examined the effect of LMWH on pregnant women without thrombophilias who had severe pregnancy complications and placental vasculopathy in an earlier pregnancy. Seventy-two women with a history of severe preeclampsia, fetal growth restriction (FGR) less than fifth percentile, severe placental abruption and/or stillbirth after 20 weeks, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 27 publications
0
33
0
2
Order By: Relevance
“…However, Mello et al [15] observed gestational age of delivery to be 37 weeks. Kupferminc et al [16] also noticed a higher gestational age of delivery in the study group.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, Mello et al [15] observed gestational age of delivery to be 37 weeks. Kupferminc et al [16] also noticed a higher gestational age of delivery in the study group.…”
Section: Discussionmentioning
confidence: 53%
“…LMWH promotes the differentiation and invasion of the trophoblast in vivo [17,18], prevents monocyte adhesion to activated endothelium [19], and inhibits tumor necrosis factor-a-induced leukocyte rolling [20]. These drugs decrease vascular resistance in vitro [21] and in vivo [15][16][17][18][19][20][21][22]. Therefore, LMWH may act by improving placental development as well as by inhibiting reactive pathways involved in Pre-eclampsia (PET) and Small for Gestation Age (SGA).…”
Section: Discussionmentioning
confidence: 99%
“…Data from these RCT's are supported by non-randomised observational studies in which non-thrombophilic women with previous obstetric complications and associated evidence of placental vasculopathy had improved obstetric outcomes when treated with LMWH in subsequent pregnancies (Kupferminc et al 2011). These studies are indeed promising and suggest the more rational use of anticoagulants using an appropriate "phenotype" driven approach (ie on the basis of disease severity and corroborating placental histopathological findings) rather than just a genotype (presence of thrombophilia) driven approach.…”
Section: The Role Of Anticoagulants In "Non-thrombophilic" Patientsmentioning
confidence: 74%
“…32 Additional studies have demonstrated that heparin can reduce the rate of PE and intrauterine growth restriction, while improving birthweight percentile and gestational age in women with a history of severe PE, as well as women with renal disease. [33][34][35][36][37] Two recent systematic reviews summarizing this literature concluded that heparin significantly reduces the recurrence of PE and was associated with significant reductions in perinatal mortality, preterm birth (before 34 and 37 weeks of gestation), and infant birth weight <10th percentile for gestational age in women considered to be at high risk of these disorders. 38,39 Although these systematic reviews were based on relatively small and heterogeneous trials, their conclusions indicate that mounting an adequately powered, multicentered trial would be warranted to assess the effectiveness of LMWH in reducing the recurrence rate of severe PE in screen-positive women.…”
Section: Novel Actions Of Low-molecular Weight Heparinmentioning
confidence: 99%